Initial teacher education by open and distance modes: A snapshot of e-competency experiences in Australia - Dobozy, Eva; Ifenthaler, D. (Open Education Europa, 2014)
This paper explores the need for greater clarity of the effectiveness of initial teacher education by open and distance modes. Reports about global teacher shortages are not new. However, the recent infograph produced by the United Nations Education, Science, and Cultural Organisation (2013) paints an alarming picture. One way to assist in the supply of sufficient qualified school teachers is to provide initial teacher education (ITE) at a distance. This paper reports on an investigation of e-competency experiences of first-year students enrolled in distance-delivered ITE. The findings from in-depth interviews by all respondents as the preferred study mode. More importantly, a number of participants reported that for them, it is the only way to gain a teaching qualilfication even though some acknowledge a lack of e-competency skills at the commencement of their studies.